2014
DOI: 10.1007/s10530-014-0759-1
|View full text |Cite|
|
Sign up to set email alerts
|

Range expansion and comparative habitat use of insular, congeneric lagomorphs: invasive European hares Lepus europaeus and endemic Irish hares Lepus timidus hibernicus

Abstract: The European hare (Lepus europaeus) has declined throughout its native range but invaded numerous regions where it has negatively impacted native wildlife. In southern Sweden, it replaces the native mountain hare (L. timidus) through competition and hybridisation. We investigated temporal change in the invasive range of the European hare in Ireland, and compared its habitat use with the endemic Irish hare (L. timidus hibernicus). The range of the European hare was three times larger and its core range twice as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 53 publications
2
44
1
2
Order By: Relevance
“…Certainly, the Irish hare shares much in common with the European hare, though the latter has a greater association with arable land, typical of its more easterly and central European distribution (Smith et al 2005). Indeed, previous studies have demonstrated that both species exhibit comparable niche breadths and almost complete niche overlap in Ireland Caravaggi et al 2015). Niche overlap metrics in the present study are, on the face of it, contradictory.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…Certainly, the Irish hare shares much in common with the European hare, though the latter has a greater association with arable land, typical of its more easterly and central European distribution (Smith et al 2005). Indeed, previous studies have demonstrated that both species exhibit comparable niche breadths and almost complete niche overlap in Ireland Caravaggi et al 2015). Niche overlap metrics in the present study are, on the face of it, contradictory.…”
Section: Discussioncontrasting
confidence: 58%
“…Our ENMs predict that most of Ireland is (and presumably was) unsuitable for the European hare, providing a potential explanation as to why most introductions failed. At present, there is a relatively range-restricted population of introduced European hares in Northern Ireland (Caravaggi et al 2015), the only region of Ireland currently predicted by our ENMs as being suitable for the species. Their range expanded three-fold between 2005 and 2012/2013 (Caravaggi et al 2015) with a core range populated solely by the invader being established recently (Caravaggi et al 2016).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations